2015
DOI: 10.1007/s10578-015-0591-6
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Psychiatric Comorbidity of Children and Adolescents Diagnosed with ADHD in Specialized Healthcare

Abstract: Recent studies have shown an increasing incidence of attention-deficit/hyperactivity disorder (ADHD) among children diagnosed in specialized services. This study aims to describe children with ADHD in Finnish specialized healthcare by reporting the demographic characteristics, time trends in diagnosis, psychiatric comorbidity, and the validity of register-based diagnoses. All the singletons born in Finland between 1991 and 2005 and diagnosed with ADHD by 2011 were identified and their psychiatric comorbidity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 52 publications
2
52
1
Order By: Relevance
“…The other most common comorbid diagnoses were : CD / ODD ( 28.1  %), anxiety disorders ( 13.6  %), autism spectrum disorders ( 11.9  %), depression ( 8.9  %,) and mental retardation ( 3.7  %). The psychiatric comorbid patterns of the sample have been reported recently in more detail [25]. These findings were in general consistent with previous studies [5].…”
Section: Methodssupporting
confidence: 91%
“…The other most common comorbid diagnoses were : CD / ODD ( 28.1  %), anxiety disorders ( 13.6  %), autism spectrum disorders ( 11.9  %), depression ( 8.9  %,) and mental retardation ( 3.7  %). The psychiatric comorbid patterns of the sample have been reported recently in more detail [25]. These findings were in general consistent with previous studies [5].…”
Section: Methodssupporting
confidence: 91%
“…The validity of the diagnosis of ADHD in the FHDR has been demonstrated. 19 The Finnish healthcare system uses the ICD-10 classification as the prevailing diagnostic system, which refers to the term 'hyperkinetic disorder', but for convenience in this article we refer to it as 'ADHD'. The term 'ADHD' for 'hyperkinetic disorder' has also been used in previous Nordic studies that use the ICD classification.…”
Section: Case Identification and Registersmentioning
confidence: 99%
“…In addition, the epidemiology and characteristics of the disease varies between genders [22] and thus different approaches for ADHD are needed for males and females [7]. Boys are known to have a greater prevalence of ADHD and are prescribed more medications than girls [2].…”
Section: Demographic Trends In Attention Deficit Hyperactivity Disordmentioning
confidence: 99%
“…Boys are known to have a greater prevalence of ADHD and are prescribed more medications than girls [2]. Joelsson et al also noted that sex distribution is different when measured in clinical versus population samples [7]. Based on a community sample, Willcutt reported that ADHD was 2-3 times more prevalent among males than females [23], while a study in a clinical sample by Nussbaum showed 2-9 fold greater diagnosis of ADHD in males [22].…”
Section: Demographic Trends In Attention Deficit Hyperactivity Disordmentioning
confidence: 99%
See 1 more Smart Citation